BASIC THINKING SYSTEM - Mayurida Nasution (Journal Analytica Islamica, 2021)
Thinking systematically (systematic thinking), means thinking about everything based on a certain method framework, there is a sequence and decision-making process. This requires obedience and discipline to the process and method to be used. Different methods of thinking will lead to different conclusions, but all of them can be accounted for because they are in accordance with a widely recognized process. The method used to obtain the data needed in this discussion is the Library Research method. The result is that to realize various scientific activities, scientific language is needed with its main elements, namely: concepts / concepts (symbols used to interpret phenomena), propositions (a statement (statement) about the nature of phenomena), theories / theories (a system of propositions). postulates or an integrated set of propositions), models (assembling a set of postulates or forming a system of propositions) and paradigms (sets of assumptions, both expressed and implied, that form the basis for scientific ideas)